Re-test of State Trait Anxiety Inventory (STAI) among engineering students in Malaysia: Reliability and validity tests - Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Herawan, Tutut; Ahmad, Othman; Suriya Kumar, Sinnadurai (Elsevier, 2011)
Various tests have been conducted using the State Trait Anxiety Inventory (STAI) and it has provided adequate evidence to measure anxiety in research and clinical settings. This paper proposes a re-test to evaluate STAI among engineering students in Malaysia. A total 253 engineering students participated in this study. The re-test was presented for reliability, construct validity, and coefficient correlation of State and Trait. The reliability coefficients were computed using Cronbach alpha. In order to determine the validity of the instrument used factor analysis and coefficient correlation were used. Results: The STAI was established with the reliability at .850. In addition, the construct validity of the STAI, as measured by factor analysis were found, the correlation between items (KMO) score .824 (>.30) and p=.000. Where, the State shows KMO=.818, p=.000, and Cronbach alpha found .797. Meanwhile, Trait proved KMO=.783, p=.000, and Cronbach alpha found .781. The results show that the reliability and validity of State Trait Anxiety Inventory was suitable and acceptable. Consistently, strong correlations between State and Trait scale scores provided supportive evidence for the instrument. The results are evident and it can be recommended as an instrument to measure anxiety level for similar studies.